2020
DOI: 10.3390/jcm9041169
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Geriatric Nutritional Risk Index on In-Hospital Mortality and Length of Hospitalization in Patients with Acute Decompensated Heart Failure with Preserved or Reduced Ejection Fraction

Abstract: In patients with heart failure (HF), the impact of the Geriatric Nutritional Risk Index (GNRI) on in-hospital mortality and length of hospital stay remains unclear. We aimed to identify the factors associated with increased in-hospital mortality and longer length of hospital stay considering the GNRI in acute decompensated HF with reduced and preserved ejection fraction (HFrEF and HFpEF, respectively). Patients with acute decompensated HF who were admitted to our institution between 2007 and 2011 were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…There are studies showing no significant differences in in-hospital mortality and the length of hospital stay between patients with GNRI <92 and ≥92, among HFrEF patients with acute decompensated HF [34]. The above results indicate the assessment of nutritional status with GNRI as useful for stratifying patients at high risk for longer length hospital stays in HFpEF but not in HFrEF [34].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…There are studies showing no significant differences in in-hospital mortality and the length of hospital stay between patients with GNRI <92 and ≥92, among HFrEF patients with acute decompensated HF [34]. The above results indicate the assessment of nutritional status with GNRI as useful for stratifying patients at high risk for longer length hospital stays in HFpEF but not in HFrEF [34].…”
Section: Discussionmentioning
confidence: 83%
“…There are studies showing no significant differences in in-hospital mortality and the length of hospital stay between patients with GNRI <92 and ≥92, among HFrEF patients with acute decompensated HF [34]. The above results indicate the assessment of nutritional status with GNRI as useful for stratifying patients at high risk for longer length hospital stays in HFpEF but not in HFrEF [34]. In our study the assessment of nutritional status with the use of the MNA form demonstrated that nutritionally sound patients were hospitalized for shorter periods of time than those at the risk of malnutrition and the malnourished, analyzed together (8.4 days vs. 5.4 days; respectively).…”
Section: Discussionmentioning
confidence: 99%
“…To illustrate the usefulness of TCBI, a comparison between other indicators proven valuable for predicting long-term outcomes and TCBI is warranted. In general, malnutrition assessed by GNRI has been reported to be associated with increased cancer mortality in patients with malignancy [9,10], and our group previously reported that the nutritional status based on GNRI was useful for stratifying ADHF patients who was at risk for prolonged hospital stay in association with HF with preserved ejection fraction [11]. However, the importance of TCBI in patients with ADHF remains to be elucidated.…”
Section: Introductionmentioning
confidence: 98%
“…Geriatric nutritional risk index (GNRI), which is based only on body weight, height, and serum albumin level, has been recently demonstrated as a very simple and objective tool to assess nutritional status in various pathological conditions [7,8]. Until now, several studies have examined the credibility of GNRI in assessing malnutrition and predicting all-cause mortality and cardiovascular (CV) events in patients on chronic hemodialysis [2,[8][9][10][11][12][13][14][15][16], peritoneal dialysis (PD) [17][18][19], non-dialysis-dependent (NDD) chronic kidney disease (CKD) [20,21], stroke [22][23][24][25], and heart failure [26][27][28].…”
Section: Introductionmentioning
confidence: 99%